Angiolymphoid Hyperplasia With Eosinophilia - Sarkar J.N; Sengupta B.N; Sadhu S.K; Bora H (Wolters Kluwer Medknow Publications, 1998)
A case of angilymphoid hyperplasia with eosinophilia is being reported for itâ€s rarity.